2006
DOI: 10.1111/j.2006.0030-1299.14396.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of forest soil fauna diversity and composition after repeated summer droughts

Abstract: J. 2006. Recovery of forest soil fauna diversity and composition after repeated summer droughts. Á Oikos 114: 496 Á506.To examine the resilience of soil animal communities to large-scale disturbances. we studied the recovery of total abundance, diversity and community composition of forest soil mesofauna after a 6-year climatic disturbance. This was done in a pre-established experiment in a Norway spruce Picea abies stand in southern Sweden in which longterm summer droughts had been experimentally imposed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 59 publications
(65 reference statements)
5
55
0
Order By: Relevance
“…Elevated CO 2 concentrations and extended droughts show a positive interaction, and elevated CO 2 can reduce the effects of drought on soil respiration [80]. In contrast, elevated CO 2 concentrations restrain diversity, but have little effect on the relative abundance or the production of a community [89]. Thus, those effects indicate the importance of a multi-factor experimental approach to understanding an ecosystem's response to droughts [18].…”
Section: Elevated Co 2 Concentrationsmentioning
confidence: 99%
“…Elevated CO 2 concentrations and extended droughts show a positive interaction, and elevated CO 2 can reduce the effects of drought on soil respiration [80]. In contrast, elevated CO 2 concentrations restrain diversity, but have little effect on the relative abundance or the production of a community [89]. Thus, those effects indicate the importance of a multi-factor experimental approach to understanding an ecosystem's response to droughts [18].…”
Section: Elevated Co 2 Concentrationsmentioning
confidence: 99%
“…Lindberg also examined what kind of long-lasting effects have been caused by draught to the community and how long the regeneration would take: he could not measure similar results even three years after the intervention comparing treated and untreated control sites. Besides, he pointed out that Oribatid mites are more sensitive and possess much moderate regeneration ability compared to Collembola or Mesostigmata (Lindberg and Bengtsson, 2006). Lindberg et al (2002 and2006) listed several supposed causes of high susceptibility: in some lifestages Oribatid mites are very sensitive to drought, larger species can not wander deeper into the soil, so they have an inferior dispersion ability.…”
Section: Introductionmentioning
confidence: 99%
“…clear-felling, burning etc.) ( and Bengtsson, (2006) showed that community regeneration following drought can not be satisfactorily measured by the sole application of total abundance. Decrease in the abundance of Oribatids can also be caused by ash treatment of sour, acidic soils (Liiri et al, 2002).…”
Section: Abundance Species Richness and Diversity -Summarymentioning
confidence: 99%
“…Short-term investigations have shown increases in springtail abundance in response to organic matter addition in agricultural areas [48] and forests [11,12], as well as decreases in abundance in response to disturbances such as tillage in agricultural systems [48] and litter removal in forest systems [49,50]. However, longer-term studies have demonstrated fairly quick recovery in abundance following disturbances [51,52]. The abundance of springtails in the litter layer is closely linked with soil moisture and temperature [12], two factors that are likely to be altered by the removal of the litter layer.…”
Section: Abundance Of Collembolamentioning
confidence: 99%
“…For example, the abundance of some species that function as fungivores are positively influenced by soil moisture and would therefore be expected to decrease in response to raking, whereas predatory species are less influenced by soil moisture and would therefore be expected to show little response to raking [12,51]. Reductions in the abundance of fungivorous mites in response to the removal of the litter layer has been demonstrated for other forest types [50].…”
Section: Occurrence Of Acarimentioning
confidence: 99%